MODERN TRENDS IN THE ERUPTION OF PERMANENT TEETH DURING THE LATE MIXED DENTITION PERIOD - Horokhovskyi, V.V.; Dienha, O.V.; Shnaider, S.A.; Gorokhivskiy, V.N.; Suslova, O.V.; Maslov, O.V.; Burdeinyi, V.S. (World of Medicine and Biology, 2024)
The study was devoted to establishing the regional terms of permanent teeth eruption in 9–12-year-old children of the city of Odesa. Dental examination was performed according to the generally accepted methodology using standard dental instruments included in the examination kit. Children were divided into groups according to their age and sex. Patients were examined on the basis of the values of age and period of teeth eruption. The results of the study indicate an earlier formation of a permanent bite in the majority of the examined children. In the examined girls, the formation of a permanent bite was completed earlier than in boys. The obtained research data should be taken into account when planning and developing a program for the prevention of major dental diseases, as well as used to establish biological maturity and determine the overall development of the child.